2008
DOI: 10.1634/stemcells.2007-0867
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of Neural Stem and Progenitor Cells in the Neural Colony-Forming Cell Assay

Abstract: Advancement in our understanding of the biology of adult stem cells and their therapeutic potential relies heavily on meaningful functional assays that can identify and measure stem cell activity in vivo and in vitro. In the mammalian nervous system, neural stem cells (NSCs) are often studied using a culture system referred to as the neurosphere assay. We previously challenged a central tenet of this assay, that all neurospheres are derived from a NSC, and provided evidence that it overestimates NSC frequency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
187
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(198 citation statements)
references
References 55 publications
10
187
0
1
Order By: Relevance
“…2A). In control cultures transduced with luc, NSC frequency fell below 6%, that is, near the value estimated in embryonic telencephalic cultures by NCFCA [56]. In these cultures, cells belonging to the neuronogenic lineage became progressively less frequent: NPs declined from 22 to 28%, neurons (Ns) from less than 5% down to 1%.…”
Section: Kinetics Of Precursor-compartment Sizes On Emx2 or Foxg1 Ovementioning
confidence: 57%
See 2 more Smart Citations
“…2A). In control cultures transduced with luc, NSC frequency fell below 6%, that is, near the value estimated in embryonic telencephalic cultures by NCFCA [56]. In these cultures, cells belonging to the neuronogenic lineage became progressively less frequent: NPs declined from 22 to 28%, neurons (Ns) from less than 5% down to 1%.…”
Section: Kinetics Of Precursor-compartment Sizes On Emx2 or Foxg1 Ovementioning
confidence: 57%
“…In fact, it has been shown that a largely predominant fraction of wild-type neurospheres does not originate from NSCs but from lineage-restricted progenitors. Among them, GPs are prominent [56] and more frequent as the culture goes ahead (Fig. 2B).…”
Section: Foxg1 Inhibits Gliogenesis and Potentiates Neuronogenesis Smentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the lack clonality of bulk cultures we have to use low-density cultures or immobilized NS [Singec et al, 2006;Mori et al, 2007;Coles-Takabe et al, 2008;Louis et al, 2008] to determine selfrenewal and multipotency. Recently, Louis et al, [2008] have suggested that at least two discreet size populations of NS form after 21 days of culture in collagen gels (immobilized NS), and that the big NS passage (self-renew), while the small NS do not. Louis et al [2008] interpret this to mean that big NS are derived from NSCs while small NS are not.…”
Section: In Vitro Culture Of Nscsmentioning
confidence: 99%
“…To confirm the presence of NSCs in the harvested SVZs of the adult mouse brain after Ara‐C treatment, we employed the neural colony‐forming cell assay (N‐CFCA) that can detect these cells based on their long‐term proliferation capabilities (Louis et al. 2008; Azari et al. 2011).…”
Section: Resultsmentioning
confidence: 99%